A Review of Contributing Factors and Challenges In Implementing Kaizen in Small and Medium Enterprises - Mohd Ghazali, Maarof; Fatimah, Mahmud (Elsevier Ltd, 2016)
The introduction of ASEAN Economic Community (AEC) in 2015 poses another challenges to the Small and Medium Enterprises (SMEs) in Malaysia to remain competitive in a larger market of ASEAN, apart from the existing effect of globalization from low cost countries such as China and India. It is important for these SMEs to remain competitive in the market since SMEs contribute significantly to the Malaysian economy. One method to improve business competitiveness is by applying the concept of continuous improvement also known as Kaizen. This paper reviews some selected factors contributing to the successful implementation of Kaizen and its challenges among small and medium enterprises. The factors such as good communication between the top management and their employees, clear corporate strategy, the presence of a Kaizen champion personnel in the organization, good knowledge management and employees empowerment were found to contribute to the successful implementation of Kaizen. The review also found that resistance to change, failure to motivate employees, lack of understanding on companies’ strategic path and difficulties in managing continuous improvement itself formed some of the challenges in implementing Kaizen. It appears some similarities exist between small and medium enterprises, and large companies interm of the contributing factors in implementing Kaizen. Thus, this paper can provides some insights into the factors contributing to successful implementation of Kaizen and its challenges. Hopefully, this paper can be beneficial to the Small and Mediun Enterprises as well as other industry players in formulating their continuous improvement or Kaizen strategies.